ANALISIS KAPASITAS TAMPUNGAN BANJIR KOLAM LUMPUR SIDOARJO - Samuel J. Sutanto (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
A simulation using the HEC-HMS model has been carried out to discover height of flood level in mainpond. The result shows that existing condition of the pond is not sufficient for controlling flood although thepond had been dredged. Flood will overflow about 0.57-0.69m above the dyke in existing condition, andabout 0.062-0.12m in dredged condition. Suggestions for prevention action are adding the amount of intakepipes, increasing dyke elevation and extending the dredging area. Flood will also occur in pond 5particularly for the return period of 10 years if BPLS does not take serious action of prevention such asdredging and increasing dyke elevation.